Middle-Late Cambrian acritarchs from the Zardkuh area in the High Zagros Mountains, southern Iran: Stratigraphic and paleogeographic implications - mohammad ghavidel- syooki (Journal of Sciences, Islamic Republic of Iran)
The excellent preservation of the acritarchs, their great abundance, diversity and good stratigraphic control permit establishment of a detailed Middle and Late Cambrian acritarch biozonation. A total of 56 palynomorph species form the basis of 10 local acritarch assemblage zones. Assemblage zones I-II occur in the lower and middle parts of the Member C of the Mila Formation and suggest Early-mid Middle Cambrian; assemblages zones III-IV appears in the upper part of the Member C of the Mila Formation and the lower part of Ilebeyk Formation and encompass latest Middle and earliest Late Cambrian; acritarch assemblage zones V-IX occur in the middle and upper parts of the Ilebeyk Formation and characterize Late Cambrian; finally, acritarch assemblage zone X appears in the basal part of the Zardkuh Formation and proves to have an early Tremadocian age. Amongst the Late Cambrian acritarch assemblages of Laurentia only the two cosmopolitan species of Timofeevia phosphoritica and Vulcanisphaera turbata are shared with coeval strata in the High Zagros Mountains.Iranian acritarch assemblages show a marked Gondwanan paleobiogeographical affinity, share a high proportion of taxa with typical Baltican and North Africa–Gondwanan assemblages, and are different from known Laurentian microphytoplankton suites. These results are in general agreement with paleogeographical models that place Avalonia, Baltica, and the North African part of Gondwana, at relatively high southern paleolatitudes, whereas Laurentia occupies a sub-equatorial position. Four new acritarch species, namely Leiosphaeridia iranense, Navifusa reticulata, Ooidium zagrosensis, and Veryhachium ilebeykensis are described.